Silicon-based photoelectric cathode for urea synthesis and preparation method thereof
By modifying the palladium-copper bimetallic catalyst with a chaotic segregation structure on the surface of the silicon-based photocathode, the problems of low Faraday efficiency and high energy consumption in urea synthesis are solved, and 100% selectivity and Faraday efficiency of urea at ultra-low potential are achieved, with high industrial application prospects.
Patent Information
- Application Number
- CN202510034809.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, the Faraday synthesis of urea is less efficient and requires higher energy consumption to drive the reaction, limiting its large-scale industrial application.
Urea is synthesized by modifying a palladium-copper bimetallic catalyst with a chaotic segregation structure on the surface of the silicon-based photocathode.
It achieves 100% selectivity and Faraday efficiency of urea at ultra-low potential (0 V vs. RHE), reduces the energy consumption of urea synthesis and has high industrial application prospects.
Smart Images

Figure CN119736661A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photoelectric catalysis, and in particular relates to a silicon-based photocathode for urea synthesis and a preparation method thereof. Background Art
[0002] In recent years, the use of renewable energy to synthesize urea to replace the current high-energy urea industrial production process has become a research hotspot. However, these methods still face the problems of low Faradaic efficiency of urea products and high energy consumption to drive the reaction, which greatly limits their large-scale industrial application (JG Chen, RM Crooks, et al. Science, 2018, (360), eaar6611.). It is worth noting that the energy consumption of traditional urea synthesis is mainly attributed to the energy consumption required for the synthesis of ammonia intermediates. At present, some studies have begun to focus on synthesizing urea from nitrates or nitrites to reduce energy consumption.
[0003] In addition, silicon semiconductor materials have been used on a large scale. Based on this, the development of silicon-based photocathodes that can utilize solar energy can further reduce the energy consumption of urea synthesis. For the current research, the focus is on optimizing the interface catalytic structure of silicon-based photocathodes to further improve the conversion efficiency and selectivity of urea products. Summary of the invention
[0004] In view of the defects in the prior art, the present invention provides a silicon-based photocathode for urea synthesis and a preparation method thereof. The silicon-based photocathode provided by the present invention exhibits excellent urea synthesis selectivity.
[0005] The preparation of the silicon-based photocathode of the present invention is achieved by the following technical scheme: A1. Dissolving a non-nitrate palladium-containing inorganic salt in a concentration range of 0 to 1 mM and a copper-containing inorganic salt in a concentration range of 0 to 1 mM in a hydrofluoric acid solution in a concentration range of 1 to 3 M to obtain a solution A; A2, cut into 0.8 cm 2 * 0.8 cm 2 A p-type semiconductor silicon wafer is immersed in solution A, reacted in a water bath at 20 to 25°C for 5 to 20 minutes, and reacted in a water bath at room temperature for a period of time, and a palladium-copper bimetallic catalyst with a chaotic segregation structure is modified on the silicon surface by a non-biased chemical etching method; A3. The back of the silicon wafer loaded with chaotic segregation palladium-copper bimetallic catalyst is fixed by bonding gallium-indium alloy, conductive silver paste and copper wire, and then encapsulated with epoxy resin, leaving only 0.3 ~ 0.6 cm on the front. 2The exposed area is naturally placed for 24 hours to allow the epoxy resin to cure, thereby obtaining a certain exposed area, thereby obtaining a silicon-based photocathode B with a chaotic segregation structure.
[0006] Preferably, in step A1, the anion in the non-nitrate palladium-containing inorganic salt is Cl - .
[0007] Preferably, in step A1, the concentration of the non-nitrate palladium-containing inorganic salt is 0.25 mM, the concentration of the copper-containing inorganic salt is 0.75 mM, and the concentration of the hydrofluoric acid is 1.5 M.
[0008] Preferably, in step A2, the water bath temperature is 20° C. and the reaction time is 20 minutes.
[0009] The silicon-based photocathode for urea synthesis prepared by the present invention is characterized in that a palladium-copper bimetallic catalyst with a chaotic segregation structure is modified on the silicon surface. The surface morphology of the silicon-based photocathode is palladium-copper nanoparticles of 20 to 100 nm, which contain both palladium-copper alloy components, copper-doped palladium components with high palladium content, and palladium-doped copper components with high copper content. The palladium-copper bimetallic catalyst with a chaotic segregation structure can realize the coupling synthesis of urea from carbon dioxide and nitrate.
[0010] The application of the silicon-based photocathode with chaotic segregation structure prepared by the present invention is used as a working electrode for photoelectrocatalytic coupling synthesis of urea by carbon dioxide and nitrate. Specifically, the silicon-based photocathode is used as a working electrode, a saturated silver / silver chloride electrode is placed in the cathode chamber as a reference electrode, and a platinum wire electrode is placed in the anode chamber as a counter electrode, and a three-electrode reaction system is built in an H-type reactor. The cathode chamber solution is a nitrate solution saturated with carbon dioxide and continuously introduced at a flow rate of 10 to 60 sccm, and the H-type reactor is separated in the middle by a Nafion-117 proton membrane. The silicon-based photocathode is subjected to a constant potential current time test (interval of -0.2 V vs. RHE) at a potential of 0 V vs. RHE to -1 V vs. RHE under standard sunlight of AM 1.5. The product in the cathode chamber is collected for product analysis.
[0011] Compared with the prior art, the present invention has the following advantages: The interface of the silicon-based photocathode prepared by the present invention is loaded with a palladium-copper bimetallic catalyst with a chaotic segregation structure. The performance can be optimized by controlling the experimental parameters. It has a high urea selectivity of 100% at a potential of 0 V vs. RHE and is an ideal unbiased industrial application material.
[0012] The present invention prepares a silicon-based photocathode loaded with a palladium-copper bimetallic catalyst with a chaotic segregation structure, and for the first time proposes and verifies the unique catalytic effect of the palladium-copper chaotic segregation structure on the coupled synthesis of urea from carbon dioxide and nitrate, with 100% urea selectivity.
[0013] The present invention uses carbon dioxide and nitrate photoelectrocatalytic coupling to synthesize urea, which has great industrial application prospects. Because the energy consumption of traditional urea synthesis is mainly attributed to the energy consumption required for the synthesis of ammonia intermediates, the use of greenhouse gas carbon dioxide and common pollutants nitrates in domestic wastewater and industrial wastewater to synthesize urea has great environmental significance and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a SEM image of the material obtained in Example 1. As can be seen from the image, the surface of the obtained silicon-based photocathode is a uniform nanoparticle morphology, and the particle size is 20-100 nm.
[0015] Figure 2 This is the XRD pattern of the material obtained in Example 1. As can be seen from the figure, the surface of the obtained silicon-based photocathode has peaks corresponding to silicon, palladium-copper alloy, copper-doped palladium, and palladium-doped copper, proving the existence of a chaotic segregation structure.
[0016] Figure 3 is the Faradaic efficiency of the target product urea obtained in Example 1. As can be seen from the figure, the synthesis performance of urea by the obtained silicon-based photocathode is verified. And the Faradaic efficiency of urea production at an ultra-low potential of 0 V vs. RHE reaches 100%. ; Figure 4 This is the XRD pattern of the material obtained in Example 2. As can be seen from the figure, only peaks corresponding to silicon and palladium-copper alloy exist on the surface of the obtained silicon-based photocathode, indicating that there is no chaotic segregation structure.
[0017] Figure 5 The Faradaic efficiency of the target product urea obtained from the material in Example 3. As can be seen from the figure, the obtained silicon-based photocathode can realize urea synthesis, and the Faradaic efficiency of urea at 0 V vs. RHE potential is 68%, which is lower than that in Example 1.
[0018] Figure 6 The Faradaic efficiency of the target product urea obtained by the material in Example 4. As can be seen from the figure, the obtained silicon-based photocathode can realize urea synthesis, and the Faradaic efficiency of urea at 0 V vs. RHE potential is 48%, which is lower than that of Example 1.
[0019] Figure 7 The absorbance curves of different urea concentrations measured by UV-Vis spectrophotometer are shown in Figure 1. As can be seen from the figure, urea concentration is positively correlated with absorbance. In order to achieve standard quantitative analysis of urea, a linear regression equation was further used for analysis.
[0020] Figure 8 The following is the standard curve of UV-visible absorbance corresponding to different concentrations of urea. As can be seen from the figure, the linear relationship between urea concentration and absorbance is excellent, indicating that this method has considerable credibility in detecting urea content. DETAILED DESCRIPTION
[0021] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0022] Example 1 This embodiment involves immersing a p-type semiconductor silicon wafer in a hydrofluoric acid solution containing palladium chloride and copper sulfate, and then preparing a silicon-based photocathode with a chaotic segregation structure by a non-biased chemical etching method, and performing urea synthesis application. The method includes the following steps: 1.1971 mg CuSO4, 0.4433 mg PdCl2, and 0.6696 mL 40wt% HF solution were added to 10 mL deionized water to obtain solution A; the molar concentration of the CuSO4 was 0.75 mM, the molar concentration of PdCl2 was 0.25 mM, and the concentration of HF was 1.5 M. The palladium chloride can be replaced by other non-nitrate palladium-containing inorganic salts.
[0023] Cut the p-type silicon wafer into 0.8 cm*0.8 cm, immerse it in solution A obtained in step 1), and react it in a 20 ℃ water bath for 20 min.
[0024] The back of the silicon wafer obtained in step 2) was bonded with copper wire by adding gallium-indium alloy, conductive silver paste, and encapsulated with epoxy resin, leaving only 0.34 cm 2 The front exposed area is obtained by cathode B.
[0025] The cathode B obtained in step 3) was used as the working electrode, and the silver / silver chloride electrode was used as the reference electrode and placed in the cathode chamber, and the platinum wire was used as the anode and placed in the anode chamber to build a three-electrode system in the H-type reaction cell. 70 mL of a mixed solution of 0.2 M potassium bicarbonate and 0.1 M potassium nitrate saturated with carbon dioxide was added to the cathode chamber, and carbon dioxide was continuously introduced into the cathode chamber at a flow rate of 30 sccm. 70 mL of a mixed solution of 0.2 M potassium bicarbonate and 0.1 M potassium nitrate was added to the anode chamber. The H-type reaction cell was separated by a Nafion-117 proton membrane in the middle. In the potential range of 0 V vs. RHE to -1 V vs. RHE, the It test was performed at intervals of -0.2 V vs. RHE, the products in the cathode chamber were collected, and the products were analyzed.
[0026] Figure 1 This is a SEM image of the material obtained in Example 1. As can be seen from the image, the surface of the obtained silicon-based photocathode is a uniform nanoparticle morphology, and the particle size is 20 nm-100 nm. Figure 2 This is the XRD pattern of the material obtained in Example 1. As can be seen from the figure, the surface of the obtained silicon-based photocathode has peaks corresponding to silicon, palladium-copper alloy, copper-doped palladium, and palladium-doped copper, proving the existence of a chaotic segregation structure. Figure 3 The Faradaic efficiency of the material obtained in Example 1 for the target product urea. As can be seen from the figure, the synthesis performance of the obtained silicon-based photocathode for urea is verified. And the Faradaic efficiency of urea production at an ultra-low potential of 0 V vs. RHE reaches 100%.
[0027] Example 2 The method of this comparative example is the same as that of Example 1, the only difference being that palladium nitrate is used as the palladium-containing inorganic salt in step 1).
[0028] Figure 4 This is the XRD pattern of the material obtained in Example 2. As can be seen from the figure, only peaks corresponding to silicon and palladium copper alloy exist on the surface of the obtained silicon-based photocathode, indicating that there is no chaotic segregation structure. The obtained silicon-based photocathode does not show urea synthesis performance.
[0029] Example 3 The method of this embodiment is the same as that of embodiment 1, except that in step 1), the concentration of palladium chloride is changed to 0.5 mM, and the concentration of copper sulfate is changed to 0.5 mM.
[0030] Figure 5 The Faradaic efficiency of the target product urea obtained from the material in Example 3. As can be seen from the figure, the obtained silicon-based photocathode can realize urea synthesis, and the Faradaic efficiency of urea at 0 V vs. RHE potential is 68%, which is lower than that in Example 1.
[0031] Example 4 The method of this embodiment is the same as that of embodiment 1, except that in step 1), the concentration of palladium chloride is changed to 0.75 mM, and the concentration of copper sulfate is changed to 0.25 mM.
[0032] Figure 6 The Faradaic efficiency of the target product urea obtained from the material in Example 4. As can be seen from the figure, the obtained silicon-based photocathode can realize urea synthesis, and the Faradaic efficiency of urea at 0 V vs. RHE potential is 48%, which is lower than that of Example 1.
[0033] Product analysis method The diacetyl monoxime method is used to determine urea. The specific steps are as follows: Solution A was obtained by mixing 10 mL of concentrated phosphoric acid, 30 mL of concentrated sulfuric acid, and 60 mL of deionized water, and then dissolving 10 mg of ferric chloride in the above solution.
[0034] Solution B was obtained by dissolving 0.5 g of diacetyl monoxime and 10 mg of thiosemicarbazide in 100 mL of deionized water.
[0035] Prepare a series of urea standard solutions (0.1 ppm, 0.2 ppm, 0.4 ppm, 0.5 ppm, 1 ppm, 2 ppm, 5ppm, 10 ppm).
[0036] Add 2 mL of solution A and 1 mL of solution B to 1 mL of the test solution containing urea and shake vigorously to mix. Then place the solution in a 100 °C oil bath for 20 min. After cooling to room temperature, obtain the absorbance at 525 nm using a UV-visible spectrophotometer.
[0037] Figure 7 The absorbance curves of different urea concentrations measured by UV-Vis spectrophotometer are shown in Figure 1. As can be seen from the figure, urea concentration is positively correlated with absorbance. In order to achieve standard quantitative analysis of urea, a linear regression equation was further used for analysis. Figure 8 The following is the standard curve of UV-visible absorbance corresponding to different concentrations of urea. As can be seen from the figure, the linear relationship between urea concentration and absorbance is excellent, indicating that this method has considerable credibility in detecting urea content.
[0038] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A silicon-based photocathode for urea synthesis and a preparation method thereof, characterized in that A palladium-copper catalyst with a chaotic segregation structure was modified on the silicon interface to prepare a silicon-based photocathode, which achieved the catalytic coupling of carbon dioxide and nitrate to synthesize urea.
2. The method for preparing the silicon-based photocathode according to claim 1, characterized in that The preparation is carried out by an unbiased chemical deposition method, and the specific preparation process includes the following steps: A1, dissolving a palladium-containing inorganic salt and a copper-containing inorganic salt together in a hydrofluoric acid solution to obtain a solution A; A2, immersing a p-type semiconductor silicon wafer in the solution A and reacting it in a 20°C water bath for 20 min.
3. The method for preparing a silicon-based photocathode according to claim 2, characterized in that: In the step A1, the palladium-containing inorganic salt cannot be a nitrate.
4. The method for preparing a silicon-based photocathode according to claim 2, characterized in that: In the step A1, the concentration of the palladium-containing inorganic salt is 0.25 mM to 10 mM, the concentration of the copper-containing inorganic salt is 0.25 mM to 10 mM, and the concentration of the hydrofluoric acid is 1 to 3 M.
5. A silicon-based photocathode loaded with a palladium-copper bimetallic catalyst having a chaotic segregation structure is prepared according to claims 1-4, characterized in that: Palladium-copper nanoparticles with a size of 20 to 100 nm and a certain stoichiometric ratio are formed at the silicon interface, and the stoichiometric ratio ranges from 1% to 99%. The chaotic segregation structure of the palladium-copper bimetallic catalyst is characterized by the presence of a palladium-copper alloy component with the same palladium-copper ratio as the total stoichiometric ratio, a copper-doped palladium component with a palladium content higher than the total stoichiometric ratio, and a palladium-doped copper component with a copper content higher than the total stoichiometric ratio.
6. The silicon-based photocathode with chaotic segregation palladium-copper bimetallic catalyst prepared according to claims 1-5 realizes the catalytic coupling synthesis of urea by carbon dioxide and nitrate, characterized in that: The silicon-based photocathode can realize the coupling synthesis of urea by carbon dioxide and nitrate under standard sunlight of AM 1.5 and in a nitrate solution saturated with carbon dioxide and continuously introduced with carbon dioxide.
7. The nitrate solution saturated with carbon dioxide and continuously fed with carbon dioxide according to claim 6, characterized in that: The nitrate concentration is 0.1-1 M, the rate of continuous introduction of carbon dioxide is 10-60 sccm, and the introduction continues after carbon dioxide reaches saturation.
Citation Information
Cited By
Unbiased coupling photoelectrochemical system and preparation method and application of anode and cathode of unbiased coupling photoelectrochemical system
CN120738701A